Secondary battery
The use of uncoated and carbon-coated artificial graphite in the negative electrode, combined with Al-doped and Zr-coated lithium cobalt oxide in the positive electrode, addresses structural issues in secondary batteries, enhancing life characteristics and enabling rapid charging.
Patent Information
- Application Number
- JP2022568472
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-28
- Filing Date
- 2021-12-28
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-12-28
AI Technical Summary
Conventional secondary battery manufacturing methods result in non-uniform pore structures and increased resistance due to fine powder generation, leading to decreased negative electrode adhesion, high temperature storage performance deterioration, and reduced life characteristics, especially when using lithium cobalt oxide as the positive electrode active material.
A secondary battery design incorporating a negative electrode with both uncoated and carbon-coated artificial graphite, and a positive electrode with lithium cobalt oxide having a bimodal particle size distribution, Al doping, and a Zr surface coating, to enhance stability and reduce lithium ion diffusion resistance.
The improved battery design significantly enhances life characteristics and enables rapid charging by stabilizing the electrode structures and reducing resistance to lithium ion movement, resulting in superior capacity retention rates.
Smart Images

Figure 0007614227000001 
Figure 0007614227000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a secondary battery having improved life characteristics.
[0002] This application claims priority to Korean Patent Application No. 10-2020-0185310, filed on December 28, 2020, and the entire contents disclosed in the specification and drawings of the relevant application are incorporated herein by reference. [Background technology]
[0003] As technological development and demand for mobile devices increases, the demand for rechargeable, compact, and high-capacity secondary batteries is rapidly increasing. Among secondary batteries, lithium secondary batteries, which have high energy density and voltage, have been commercialized and are widely used.
[0004] A lithium secondary battery is constructed by impregnating an electrolyte containing a lithium salt in an electrode assembly having a porous separator between a positive electrode and a negative electrode, each of which is coated with an active material on an electrode collector. The electrode is manufactured by applying a slurry, in which the active material, a binder, and a conductive material are dispersed in a solvent, to a current collector, followed by drying and pressing.
[0005] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator.
[0006] The negative electrode includes a negative electrode active material that inserts and extracts lithium ions released from the positive electrode. The negative electrode active material may be a graphite-based active material, for example, natural graphite or artificial graphite.
[0007] The artificial graphite is mainly used in the form of secondary particles, and for this purpose, coke, which is a material for primary particles, is generally coarsened to produce secondary particles, which are then graphitized by heat treatment to obtain artificial graphite in the form of secondary particles.
[0008] However, in the case of the conventional manufacturing method in which the size of the primary particles is not controlled, a large amount of fine powder that is not coarsened or that is separated from the secondary particles even after coarsening is generated. This reduces the negative electrode adhesive strength (resistance to the negative electrode active material particles being detached from the negative electrode) in the manufactured negative electrode, which may deteriorate the high-temperature storage performance of the battery. In addition, since the fine powder is also contained in the secondary particles, the pores of the negative electrode are not uniform, which increases the pore resistance of the negative electrode, thereby deteriorating the life characteristics and quick charging performance of the battery.
[0009] Meanwhile, lithium cobalt oxide (LiCoO2), ternary system (NMC / NCA), LiMnO4, LiFePO4, etc. are used as positive electrode active materials for secondary batteries. Among these, LiCoO2 has the problem that the price of cobalt is expensive and the capacity is lower than that of ternary systems at the same voltage, so the use of ternary systems is gradually increasing in order to increase the capacity of secondary batteries.
[0010] However, LiCoO2 is still widely used due to its excellent physical properties such as high rolling density, and excellent electrochemical properties such as high cycle characteristics. However, LiCoO2 has a low charge / discharge current of about 150mAh / g, and at voltages of 4.3V or higher, its crystal structure is unstable, causing a rapid drop in life characteristics, and there is a risk of fire due to reaction with the electrolyte.
[0011] In particular, when high voltage is applied to develop high capacity secondary batteries, the possibility of surface and structural instability increases as the Li content of LiCoO2 increases.
[0012] Therefore, there is still a need to develop technology that utilizes the excellent properties of artificial graphite as the negative electrode active material and lithium cobalt oxide (LiCoO2) as the positive electrode active material while improving the life characteristics of secondary batteries. Summary of the Invention [Problem to be solved by the invention]
[0013] The present invention has been made in consideration of the above problems, and has an object to provide a secondary battery with improved life characteristics. [Means for solving the problem]
[0014] The present invention has been made in view of the above problems, and according to one aspect of the present invention, there is provided a method for manufacturing a secondary battery according to the following embodiment.
[0015] According to the first embodiment, A secondary battery comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector and including a positive electrode active material and a binder; The positive electrode active material includes lithium cobalt oxide, The lithium cobalt oxide has a bimodal average particle size distribution including two different average particle sizes, The lithium cobalt oxide includes Al doping and is surface coated with Zr; the negative electrode comprises a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector and including a negative electrode active material and a binder; The negative electrode active material includes a first negative electrode active material which is artificial graphite without a carbon coating layer on its surface, and a second negative electrode active material which is artificial graphite with a carbon coating layer on its surface.
[0016] According to the second embodiment, in the first embodiment, The lithium cobalt oxide may include large particles having an average particle size of 11 μm to 30 μm and small particles having an average particle size of 1 μm to 10 μm.
[0017] According to the third embodiment, in the first or second embodiment, The content of Al doped in the lithium cobalt oxide may be 1,000 to 10,000 ppm.
[0018] According to a fourth embodiment, in any one of the first to third embodiments, The content of Zr coated on the surface of the lithium cobalt oxide may be 1 to 5,000 ppm.
[0019] According to the fifth embodiment, in any one of the first to fourth embodiments, The weight ratio of the first negative electrode active material to the second negative electrode active material may be 1:99 to 99:1.
[0020] According to the sixth embodiment, in any one of the first to fifth embodiments, The negative electrode active material layer may be a single layer including the first negative electrode active material and the second negative electrode active material.
[0021] According to the seventh embodiment, in any one of the first to sixth embodiments, The negative electrode active material layer may be a double layer including a lower layer region including the first negative electrode active material and an upper layer located above the lower layer region and including the second negative electrode active material.
[0022] According to the eighth embodiment, in any one of the first to seventh embodiments, The content of the carbon coating layer may be 0.5 wt % to 10.0 wt % based on the total weight of the artificial graphite having the carbon coating layer. Effect of the Invention
[0023] According to an embodiment of the present invention, artificial graphite, which is a representative negative electrode active material, and lithium cobalt oxide (LiCoO2), which is a positive electrode active material, are used in the past. In order to improve these problems, a negative electrode using both uncoated artificial graphite and carbon-coated artificial graphite as a negative electrode active material and a positive electrode including a positive electrode active material having a bimodal particle size distribution with different average particle sizes, in which lithium cobalt oxide is doped with a certain amount of Al and coated with Zr as a positive electrode active material, are provided. This improves the durability of the positive electrode active material and reduces the cell diffusion resistance, i.e., the resistance generated when lithium ions move, thereby providing a secondary battery with significantly improved life characteristics and advantageous effects on fast charging.
[0024] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited to only the matters described in the drawings. [Brief description of the drawings]
[0025] [Figure 1] 1 is a graph showing the capacity retention rates of the lithium secondary batteries of Example 1 and Comparative Examples 1 and 2. [Diagram 2] 1 is a graph showing the capacity retention rates of the lithium secondary batteries of Example 2 and Comparative Examples 3 and 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the attached drawings. Prior to this, the terms and words used in the specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts corresponding to the technical ideas of the present invention, in accordance with the principle that the inventor himself can appropriately define the concepts of terms in order to best describe the invention.
[0027] According to one aspect of the invention, A secondary battery comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector and including a positive electrode active material and a binder; The positive electrode active material includes lithium cobalt oxide, The lithium cobalt oxide has a bimodal average particle size distribution including two different average particle sizes, The lithium cobalt oxide contains 5,000 ppm or more of Al doping and is surface coated with Zr; the negative electrode comprises a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector and including a negative electrode active material and a binder; The negative electrode active material includes a first negative electrode active material which is artificial graphite without a carbon coating layer on its surface, and a second negative electrode active material which is artificial graphite with a carbon coating layer on its surface.
[0028] Artificial graphite, which is used as the negative active material for secondary batteries, is manufactured by mixing coke with a binder and sintering and heating it at high temperatures of over 2,500℃, and the crystallinity is intentionally increased during the manufacturing process, resulting in a consistent and stable internal structure.Compared to natural graphite, it does not hold as many lithium ions, but has the advantage of a relatively long charge / discharge life.
[0029] However, artificial graphite is mainly used in the form of secondary particles. For this purpose, coke, which is usually a material for primary particles, is coarsened to produce secondary particles, which are then graphitized by heat treatment to obtain artificial graphite in the form of secondary particles.
[0030] In the conventional manufacturing method where the size of the primary particles is not controlled, a large amount of fine powder that is not coarsened or that is separated from the secondary particles even after coarsening is generated. This reduces the negative electrode adhesion (resistance to the negative electrode active material particles being detached from the negative electrode) in the manufactured negative electrode, which may result in poor high-temperature storage performance of the battery. In addition, since the fine powder is also contained in the secondary particles, the pores of the negative electrode are not uniform, which increases the pore resistance of the negative electrode, thereby deteriorating the life characteristics and fast charging performance of the battery. To solve this problem, a process of disposing a carbon coating layer on the secondary particles has been used.
[0031] In the present invention, the negative electrode active material includes a first negative electrode active material which is artificial graphite without a carbon coating layer on its surface, and a second negative electrode active material which is artificial graphite with a carbon coating layer on its surface.
[0032] In comparison with the case where only artificial graphite without a carbon coating layer on its surface is used alone as the negative electrode active material, or only artificial graphite with a carbon coating layer on its surface is used alone as the negative electrode active material, when a first negative electrode active material which is artificial graphite without a carbon coating layer on its surface and a second negative electrode active material which is artificial graphite with a carbon coating layer on its surface are used together as the negative electrode active material according to the present invention, cell diffusion resistance is reduced, thereby improving the life characteristics and enabling rapid charging.
[0033] The artificial graphite is generally produced by carbonizing raw materials such as coal tar, coal tar pitch, and petroleum-based medium oil at 2,500°C or higher, and is used as an anode active material after such graphitization and particle size adjustment such as crushing and secondary particle formation. In the case of artificial graphite, crystals are randomly distributed within the particles, and it has a lower sphericity and a slightly pointed shape compared to natural graphite.
[0034] The artificial graphite used in one embodiment of the present invention includes mesophase carbon microbeads (MCMB), mesophase pitch-based carbon fiber (MPCF), artificial graphite graphitized in a block form, artificial graphite graphitized in a powder form, etc., which are commonly used commercially. The artificial graphite preferably has a sphericity of 0.91 or less, preferably 0.6 to 0.91, and more preferably 0.7 to 0.9.
[0035] The first negative electrode active material, i.e., secondary particles of artificial graphite without a carbon coating layer, may be formed by coarsening primary particles, that is, the secondary particles may be structures formed by agglomeration of the primary particles through a coarsening process.
[0036] The second negative electrode active material may include a carbon coating layer on a surface of the secondary particle, and the carbon coating layer may include at least one of amorphous carbon and crystalline carbon.
[0037] The crystalline carbon may further improve the conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fullerene, carbon nanotube, and graphene.
[0038] The amorphous carbon can appropriately maintain the strength of the coating layer and improve the output characteristics and fast charging performance of the artificial graphite. The amorphous carbon can be a carbon-based material formed by using at least one carbide selected from the group consisting of tar, pitch, and other organic substances, or a hydrocarbon as a source in a chemical vapor deposition process.
[0039] The other carbonized organic matter may be a carbonized organic matter selected from carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose or ketohexose, and combinations thereof.
[0040] The hydrocarbon may be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The aliphatic or alicyclic hydrocarbon of the substituted or unsubstituted aliphatic or alicyclic hydrocarbon may be methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, hexane, etc. The aromatic hydrocarbon of the substituted or unsubstituted aromatic hydrocarbon may be benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, phenanthrene, etc.
[0041] The carbon coating layer may be included in an amount of 0.5 wt % to 10.0 wt %, specifically, 1 wt % to 8 wt %, or 2 wt % to 6 wt %, based on the total weight of the second negative active material. When the amount is within this range, the capacity per weight of the negative active material particles is ensured, while the fast charging performance of the artificial graphite can be improved.
[0042] The first negative electrode active material, which is the artificial graphite not having a carbon coating layer on its surface, may have a D50 of 5 μm to 35 μm, specifically 7 μm to 33 μm, and more specifically 10 μm to 30 μm.
[0043] The second negative electrode active material, which is the artificial graphite having a carbon coating layer on its surface, may have a D50 of 4 μm to 32 μm, specifically 6 μm to 30 μm, and more specifically 8 μm to 28 μm or 8 μm to 21 μm.
[0044] According to an embodiment of the present invention, the weight ratio of the first negative electrode active material to the second negative electrode active material may be 1:99 to 99:1, or 20:80 to 80:20, or 30:70 to 70:30, or 30:70 to 50:50, or 50:50 to 70:30. When the weight ratio of the first negative electrode active material to the second negative electrode active material satisfies such a range, the battery diffusion resistance is advantageously reduced.
[0045] According to an embodiment of the present invention, the negative electrode active material layer may be a single layer including the first and second negative electrode active materials.
[0046] In addition, the negative electrode active material layer may be a double layer including a lower layer region including the first negative electrode active material and an upper layer located on the lower layer region and including the second negative electrode active material.
[0047] When the negative electrode active material layer is a double layer, since the first negative electrode active material contained in the lower layer region and the second negative electrode active material contained in the upper layer region of the negative electrode are different in type / form, a mixed region (intermixing) where these different types of active materials are mixed may exist at the portion where the lower layer region and the upper layer region abut against each other. This is because, when a lower layer slurry including the first negative electrode active material and an upper layer slurry including the second negative electrode active material are coated on a current collector simultaneously or successively with a very short time difference and then simultaneously dried to form an active material layer, a certain mixed region is generated at the interface where the lower layer slurry and the upper layer slurry abut against each other before drying, and the mixed region is formed into a layer shape of the mixed region while being dried later.
[0048] In one embodiment of the present invention, the weight ratio (ratio of load per unit area) of the lower layer region to the upper layer region of the active material layer may be 20:80 to 80:20, more specifically, 30:70 to 70:30. When this weight ratio range is satisfied, the adhesive strength is increased and excellent fast charging performance can be exhibited.
[0049] In an embodiment of the present invention, the thickness ratio of the upper layer region to the lower layer region may be 20:80 to 80:20, and more particularly, 30:70 to 70:30. When the thickness ratio is within this range, the adhesive strength is increased and excellent fast charging performance can be exhibited.
[0050] In an embodiment of the present invention, the total thickness of the negative electrode active material layer is not particularly limited and may be, for example, 40 to 200 μm. In addition, the thickness of the lower layer region of the active material layer may be 20 to 150 μm or 30 to 100 μm, and the thickness of the upper layer region of the active material layer may be 20 to 150 μm or 30 to 100 μm.
[0051] In this case, when the thickness ratio of the upper layer region to the lower layer region satisfies this range, it is advantageous in terms of improving the quick charging characteristics.
[0052] In an embodiment of the present invention, the negative electrode current collector used as a substrate for forming the active material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used.
[0053] The thickness of the current collector is not particularly limited, but may be a commonly applied thickness of 3 to 500 μm.
[0054] The binder polymer contained in the negative electrode active material layer may be various types of binder polymers such as polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HEP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, styrene butylene glycol (SBR), fluororubber, various copolymers, etc. When the negative electrode active material layer is a double layer, the binder polymers contained in each layer may be the same or different.
[0055] In addition, the negative electrode active material layer of the present invention may further include a thickener. Specific examples of the thickener include carboxymethyl cellulose (CMC), carboxyethyl cellulose, polyvinylpyrrolidone, etc. When the negative electrode active material layer is a double layer, the thickeners contained in each layer may be the same or different.
[0056] The active material layer may further include a conductive material. The conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity. For example, carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as fluorocarbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used. When the negative electrode active material layer is a double layer, the conductive materials contained in each layer may be the same or different.
[0057] According to one aspect of the present invention, when the negative electrode has a single layer structure, the negative electrode may be manufactured by preparing a slurry including a first negative electrode active material, a second negative electrode active material, a binder polymer, and a dispersion medium, and coating and drying the slurry on a negative electrode current collector.
[0058] In addition, when the negative electrode has a double layer structure, the method for producing the negative electrode includes the steps of: preparing a lower layer slurry including a first negative electrode active material, a first binder polymer, and a first dispersion medium, and preparing an upper layer slurry including a second negative electrode active material, a second binder polymer, and a second dispersion medium; coating one surface of a negative electrode current collector with the lower layer slurry, and coating the upper layer slurry on the lower layer slurry; and drying the coated underlayer slurry and overlayer slurry simultaneously to form an active material layer.
[0059] The active material (first negative electrode active material, second negative electrode active material), binder polymer (first binder polymer, second binder polymer), alternative thickener (first thickener, second thickener), conductive material, etc. contained in the lower layer slurry and the upper layer slurry are the same as those described above.
[0060] The dispersion medium (first dispersion medium and second dispersion medium) may be N-methylpyrrolidone, acetone, water, or the like, each of which may be used independently.
[0061] In this case, the lower layer region of the negative electrode active material layer of the present invention is formed from the coated lower layer slurry, and the upper layer region of the negative electrode active material layer of the present invention is formed from the upper layer slurry.
[0062] According to one embodiment of the present invention, the lower layer slurry may be coated, and then the upper layer slurry may be coated on the lower layer slurry at the same time or after a predetermined time lag. In this case, an apparatus such as a double slot die may be used.
[0063] The step of simultaneously drying the coated lower layer slurry and the coated upper layer slurry to form an active material layer may include simultaneously drying the coated lower layer slurry and the coated upper layer slurry to remove a dispersion medium in the slurry, rolling the slurry, and then vacuum drying the slurry to form an active material layer.
[0064] In this case, the rolling may be performed by a method commonly used in the art, such as roll pressing, at a pressure of 1 to 20 MPa and a temperature of 15 to 30° C. In addition, the rolling may be performed under conditions such that the porosity of the electrode (active material layer) after rolling is 20 to 40%, or 25 to 35%, or 20 to 30%, or 30 to 40%.
[0065] The step of drying the coated slurry may be performed at, for example, 70 to 90° C., or 75 to 85° C., or 80 to 85° C. for 10 to 30 minutes, or 15 to 25 minutes, or 20 to 30 minutes, and the drying temperature and time can be appropriately adjusted depending on the type and content of the dispersion medium.
[0066] In addition, the dried slurry layer may be rolled and then vacuum dried at a temperature of 100 to 170°C, 120 to 150°C, or 130 to 150°C for about 3 to 10 hours or 5 to 8 hours, and the drying temperature and time may be appropriately adjusted depending on the type and content of the dispersion medium.
[0067] In the negative electrode active material layer, the total proportion (wt %) of the binder polymer may be 1 to 3 wt %, or 1 to 2 wt %, or 2 to 3 wt %.
[0068] When the negative electrode active material layer has a double layer structure, the ratio of the weight percentage of the first binder polymer in the lower layer region to the weight percentage of the second binder polymer in the upper layer region may be 1 to 5, or 1.2 to 4, or 1.5 to 3, or 2.1 to 3.
[0069] In this way, when the ratio of the weight percent of the first binder polymer in the lower layer region to the weight percent of the second binder polymer in the upper layer region satisfies the above range, excellent adhesive strength and fast charging performance can be exhibited.
[0070] The weight percentage of the first binder polymer in the lower layer region may be 2 to 4 weight percent, or 2.3 to 3 weight percent, and the weight percentage of the second binder polymer in the upper layer region may be 0.5 to 2 weight percent, or 1 to 1.7 weight percent.
[0071] The positive electrode may be manufactured by mixing a positive electrode active material, a conductive material, a binder, and a solvent to prepare a slurry, which is then directly coated onto a positive electrode current collector, or by casting the slurry onto a separate support, and then laminating the positive electrode active material film peeled off from the support onto a positive electrode current collector.
[0072] The positive electrode active material is LiCoO2 (lithium cobalt oxide), and the lithium cobalt oxide has a bimodal average particle size distribution including two types of particles with different average particle sizes. The lithium cobalt oxide contains 5,000 ppm or more of Al doping and is surface-coated with Zr.
[0073] When lithium cobalt oxide is used as a positive electrode active material at high voltage, a large amount of lithium ions are released from the lithium cobalt oxide particles, causing defects in the crystal structure, which causes the unstable crystal structure to collapse and reduce reversibility. In addition, when lithium ions are released, the Co that exists on the surface of the lithium cobalt oxide particles is 3+ Or Co 4+ When the ions are reduced by the electrolyte, oxygen is released from the crystal structure, which can further promote the above-mentioned structural collapse.
[0074] Therefore, in order to stably use lithium cobalt oxide under high voltage, it is necessary to stably maintain the crystal structure even when a large amount of lithium ions are released, and to suppress side reactions between Co ions and the electrolyte.
[0075] Therefore, in the present invention, a Zr-containing coating layer is formed on the surface of lithium cobalt oxide particles, and a positive electrode active material is manufactured so that Al doping is contained in the lithium cobalt oxide. The dopant Al doped in the lithium cobalt oxide and the Zr contained in the coating layer are oxidized preferentially to cobalt (Co) under charging conditions of 4.4 V or more, and the internal structure of the positive electrode active material particles is stably maintained. Changes in the surface structure of the positive electrode active material are suppressed, and surface safety is also improved, so that the deterioration of the cycle characteristics of the secondary battery at high voltages can be effectively prevented.
[0076] In an embodiment of the present invention, the lithium cobalt oxide may have a composition represented by the following Formula 1:
[0077] [Chemical formula 1] Li aAl b Zr c Co 1-(b+c) O2 In the above Chemical Formula 1 、 0.95 ≤ a ≤ 1.05; 0 <b≦0.2; 0≦c≦0.2.
[0078] The content of Al doped in the lithium cobalt oxide may be 1,000 to 10,000 ppm, 2,000 to 9,000 ppm, 3,000 to 8,000 ppm, or 5,000 to 7,000 ppm based on the total weight of the lithium cobalt oxide. When the content of Al is within this range, the stability of the internal structure of the lithium cobalt oxide active material can be ensured, and the cycle characteristics of a secondary battery using such an active material can be improved.
[0079] In addition, the content of Zr coated on the surface of the lithium cobalt oxide may be 1 to 5,000 ppm, or 100 to 3,000 ppm, or 300 to 1,000 ppm, or 500 to 800 ppm, or 500 to 700 ppm based on the total weight of the lithium cobalt oxide. When the content of Zr satisfies such a range, it is advantageous because it can ensure the stability of the surface structure of the lithium cobalt oxide active material and improve the cycle characteristics of a secondary battery using such an active material.
[0080] In the present invention, the content of Al and Zr contained in the lithium cobalt oxide can be confirmed using a method such as an electron probe micro analyzer (EPMA) or an inductively coupled plasma-atomic emission spectrometer (ICP-AES).
[0081] The lithium cobalt oxide has a bimodal average particle size distribution including two types of particles, large and small, having different average particle sizes D50.
[0082] According to an embodiment of the present invention, the average particle size of the large particles is 3 to 30 times, or 5 to 10 times, larger than the average particle size of the small particles.
[0083] According to an embodiment of the present invention, the large particles may have an average particle size of 11 μm to 30 μm, or 15 μm to 25 μm, and the small particles may have an average particle size of 1 μm to 10 μm, or 2 μm to 9 μm.
[0084] When the average particle size of the large particles and the small particles satisfies this range, the packing density of the positive electrode can be increased.
[0085] In addition, the weight ratio of the large particles to the small particles may be 99:1 to 50:50, or 90:10 to 70:30, or 90:10 to 80:20. When the weight ratio of the large particles to the small particles satisfies such a range, the packing density of the positive electrode increases, and the cell energy density (secondary battery energy density) can be improved.
[0086] The average particle size D50 is the particle size at the 50% point of the cumulative particle number distribution based on particle size.
[0087] The D50 can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) to measure the difference in diffraction pattern depending on the particle size when the particles pass through a laser beam, and calculate the particle size distribution. The D50 can be measured by calculating the diameter of the particle at the point where the particle number cumulative distribution by particle size in the measuring device is 50%.
[0088] According to an embodiment of the present invention, a method for producing a positive electrode active material includes: (a) mixing a lithium precursor, a cobalt oxide, and a doping precursor containing Al, and then performing primary firing to prepare spherical lithium cobalt oxide; (b) mixing the lithium cobalt oxide of step (a) with a compound containing Zr, followed by secondary firing.
[0089] That is, in the precursor step, an appropriate amount of a doping precursor containing Al is mixed and primarily fired to prepare Al-substituted lithium cobalt oxide particles, and a compound containing Zr is applied to the surface of the Al-substituted lithium cobalt oxide particles and secondary fired to prepare a positive electrode active material having a coating layer formed thereon.
[0090] First, to prepare the positive electrode active material, a lithium precursor, a cobalt oxide, and a doping precursor containing Al are mixed together.
[0091] In an embodiment of the present invention, the mixed molar ratio of the lithium precursor (Li) and the cobalt oxide (Co) may be 1:1 to 1.05:1, and the content of the doping precursor containing Al may be 1,000 to 10,000 ppm, or 2,000 to 9,000 ppm, or 3,000 to 8,000 ppm, or 5,000 to 7,000 ppm based on the total weight of the lithium precursor (Li) and the cobalt oxide (Co).
[0092] For example, the cobalt oxide may be, but is not limited to, at least one selected from the group consisting of Co3O4, CoCO3, Co(NO3)2, and Co(OH)2.
[0093] The lithium precursor is not limited as long as it is a compound containing a lithium source, and may be at least one selected from the group consisting of Li2CO3, LiOH, LiNO3, CH3COOLi, and Li2(COO)2.
[0094] The doping precursor containing Al may be at least one selected from the group consisting of metals, metal oxides, and metal salts. The metal salts may include, but are not limited to, acetates, nitrates, and sulfates of the metal Al.
[0095] Then, the mixture of the lithium precursor, the cobalt oxide, and the doping precursor containing Al is primarily fired to produce spherical lithium cobalt oxide.
[0096] The primary firing may be carried out at 800° C. to 1200° C. for 8 to 12 hours.
[0097] Next, the lithium cobalt oxide resulting from the first firing is mixed with a compound containing Zr, and then the mixture is subjected to a second firing.
[0098] The Zr-containing compound forming the coating layer may include, for example, ZrO2, ZrO, Li2ZrO3, or two or more of these, but is not limited thereto.
[0099] In an embodiment of the present invention, the content of the Zr-containing compound may be 1 to 5,000 ppm, or 100 to 3,000 ppm, or 300 to 1,000 ppm, or 500 to 800 ppm, or 700 to 800 ppm, based on the weight of the primary calcination result.
[0100] The secondary firing may be carried out at 400° C. to 800° C. for 3 to 8 hours.
[0101] The lithium cobalt oxide having different average particle diameters, i.e., lithium cobalt oxide having Al doping and surface-coated with Zr, which has been subjected to the secondary calcination, is prepared and mixed to obtain a positive electrode active material according to an embodiment of the present invention.
[0102] According to an embodiment of the present invention, the two types of lithium cobalt oxide having different average particle sizes can be obtained by adjusting the average particle sizes of starting materials used in the preparation of the lithium cobalt oxide to different values.
[0103] For example, by using two kinds of cobalt oxides having different average particle sizes, it is possible to obtain two kinds of lithium cobalt oxides having different average particle sizes in the final product, i.e., the large particle lithium cobalt oxide having a large average particle size is derived from the large particle cobalt oxide having a large average particle size, and the small particle lithium cobalt oxide having a small average particle size is derived from the small particle cobalt oxide having a small average particle size.
[0104] The positive electrode current collector is not particularly limited as long as it is generally manufactured to a thickness of 3 to 300 μm, does not induce chemical changes in the battery, and has high conductivity. For example, any one selected from stainless steel, aluminum, nickel, titanium, and aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver may be used, and more specifically, aluminum may be used. The current collector may have fine irregularities on its surface to increase the adhesive strength of the positive electrode active material, and may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0105] Meanwhile, the conductive material, binder and solvent may be appropriately selected from those exemplified in the production of the negative electrode.
[0106] The present invention uses artificial graphite, which is a representative anode active material, and lithium cobalt oxide (LiCoO2), which is a cathode active material, and in order to improve these problems, the present invention simultaneously provides an anode using both uncoated artificial graphite and carbon-coated artificial graphite as an anode active material, and a cathode including a cathode active material in which a certain amount of Al is doped into lithium cobalt oxide and Zr is coated thereon, and the cathode active material has a bimodal particle size distribution with different average particle sizes. As a result, the secondary battery of the present invention, which simultaneously includes such an anode and a cathode, has improved structural stability of the cathode by inserting Al into the lithium cobalt oxide and replacing it with Co or Li ions in the cathode active material, and has significantly improved life characteristics due to reduced resistance during lithium ion movement, and can provide a secondary battery with excellent fast charging characteristics by using carbon-coated artificial graphite.
[0107] The separator may be a conventional porous polymer film used in a conventional separator, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, either alone or in combination. Also, an insulating thin film having high ion permeability and mechanical strength may be used. The separator may include a safety reinforced separator (SRS) in which a ceramic material is thinly coated on the surface of the separator. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, polyethylene terephthalate fiber, or the like, may be used, but is not limited thereto.
[0108] The electrolytic solution contains a lithium salt as an electrolyte and an organic solvent for dissolving the lithium salt.
[0109] The lithium salt can be used without any limitation as long as it is one that is commonly used in electrolytes for secondary batteries. For example, the anion of the lithium salt is F- , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One selected from the group consisting of:
[0110] The organic solvent contained in the electrolytic solution may be any commonly used organic solvent without limitation. Representative examples include propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, γ-butyrolactone, propylene sulfide, and tetrahydrofuran.
[0111] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate organic solvents, are preferably used since they are high-viscosity organic solvents and have a high dielectric constant, which makes it easy to dissociate lithium salts in the electrolyte. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constant, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte solution having high electrical conductivity can be prepared, which is preferable.
[0112] Optionally, the electrolyte stored according to the present invention may further contain additives such as overcharge inhibitors that are typically included in electrolytes.
[0113] According to an embodiment of the present invention, a lithium secondary battery may be manufactured by forming an electrode assembly by disposing a separator between a positive electrode and a negative electrode, and then inserting the electrode assembly into, for example, a pouch, a cylindrical battery case, or a prismatic battery case, and then injecting an electrolyte into the electrode assembly. Alternatively, the electrode assembly may be stacked, impregnated with an electrolyte, and the resulting product may be inserted into a battery case and sealed to manufacture a lithium secondary battery.
[0114] According to an embodiment of the present invention, the lithium secondary battery may be of a stacked type, a wound type, a stacked / folded type, or a cable type.
[0115] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a plurality of battery cells. Preferred examples of the medium- to large-sized devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems, and can be particularly useful in hybrid electric vehicles and new energy storage batteries, which are areas where high output is required.
[0116] The present invention will be described in detail below with reference to examples to aid in understanding the present invention. However, the embodiments according to the present invention can be modified in various ways, and the scope of the present invention is not limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those with average knowledge in the art.
[0117] Example 1: Manufacture of secondary battery <Production of negative electrodes> A first negative electrode active material was prepared, which was an artificial graphite having a form of secondary particles formed by coarsening primary particles of artificial graphite and no carbon coating layer, and a second negative electrode active material was prepared, which was an artificial graphite having a carbon coating layer disposed on secondary particles formed by coarsening primary particles of artificial graphite. In this case, the D50 of the primary particles was 10 μm, and the average particle size D50 of the first negative electrode active material, which was an artificial graphite having a form of secondary particles formed by coarsening primary particles, was 20 μm. In the second negative electrode active material, the carbon coating layer on the secondary particles was included in an amount of 4.0 wt % based on the total weight of the second negative electrode active material. In this case, the average particle size D50 of the second negative electrode active material was 21 μm.
[0118] The first negative electrode active material, the second negative electrode active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 48:48:1:2:1, and water was added to prepare a slurry.
[0119] The slurry was applied at 5 mAh / cm2 to one side of a 10 μm thick negative electrode current collector made of copper (Cu) foil. 2 The current collector coated with the slurry was vacuum dried at about 130° C. for 8 hours and rolled to a porosity of 30% to prepare a single-layered negative electrode.
[0120] <Production of positive electrodes> A lithium cobalt oxide having a bimodal average particle size distribution including large particles having an average particle size D50 of 16 μm and small particles having an average particle size D50 of 8 μm, doped with 5,000 ppm Al, and surface-coated with 700 ppm Zr was prepared as a positive electrode active material. The weight ratio of the large particles to the small particles was 80:20.
[0121] At this time, the contents of Al and Zr contained in the lithium cobalt oxide were confirmed using an inductively coupled plasma-atomic emission spectrometry (ICP-AES).
[0122] The positive electrode active material, polyvinylidene fluoride (PVdF) as a binder, and natural graphite as a conductive material were thoroughly mixed in N-methylpyrrolidone (NMP) in a weight ratio of 96:2:2, and then the mixture was applied to an Al foil having a thickness of 20 μm at a capacity of 5 mAh / cm. 2 The mixture was vacuum dried at about 130° C. for 8 hours and rolled to a porosity of 30% to prepare a positive electrode.
[0123] <Manufacturing lithium secondary batteries> A non-aqueous electrolyte solution was prepared by dissolving LiPF6 to a concentration of 1.0 M in an organic solvent obtained by mixing ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) in a ratio of 3:3:4 (volume ratio).
[0124] A porous polypropylene separator was interposed between the prepared positive and negative electrodes, and the electrolyte was injected into the separator to prepare a lithium secondary battery.
[0125] Comparative Example 1: Manufacturing of secondary batteries A negative electrode, a positive electrode, and a secondary battery were manufactured in the same manner as in Example 1, except that a first negative electrode active material, which is artificial graphite having a form of secondary particles formed by coarsening primary particles of artificial graphite and does not have a carbon coating layer, a conductive material, Super C65, a binder polymer, styrene butadiene rubber (SBR), and a thickener, carboxymethyl cellulose (CMC), were mixed in a weight ratio of 96:1:2:1, respectively, and water was added to prepare a slurry.
[0126] Comparative Example 2: Manufacturing of secondary batteries A negative electrode, a positive electrode, and a secondary battery were prepared in the same manner as in Example 1, except that a lithium cobalt oxide not doped with Al and not surface-coated with Zr was used as a positive electrode active material.
[0127] Example 2: Manufacture of secondary battery <Production of negative electrodes> The first negative electrode active material used in Example 1, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a first binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 95:1:1:3, and water was added to prepare a slurry for the lower layer.
[0128] The second negative electrode active material used in Example 1, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a second binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 97:1:1:1, and water was added to prepare a slurry for the upper layer.
[0129] Using a slot die, the lower layer slurry was applied at 2.5 mAh / cm to one side of a copper (Cu) foil, which is a negative electrode current collector having a thickness of 10 μm. 2 After applying the slurry for the lower layer at a loading amount of 2.5 mAh / cm2, the slurry for the upper layer was applied on the applied slurry for the lower layer. 2The current collector coated with the slurry was then dried at 80°C for 20 minutes to remove water from the slurry, and the dried slurry layer was rolled and then vacuum dried at about 130°C for 8 hours to prepare a negative electrode. The negative electrode thus prepared had a porosity of 30%, a double-layer structure of an upper layer region with a thickness of 50 μm and a lower layer region with a thickness of 50 μm, and an active material layer with a total thickness of 100 μm.
[0130] A positive electrode and a secondary battery were manufactured in the same manner as in Example 1, except that the negative electrode thus manufactured was used.
[0131] Comparative Example 3: Manufacturing of secondary battery A negative electrode, a positive electrode, and a secondary battery were manufactured in the same manner as in Example 2, except that a lithium cobalt oxide not doped with Al and not surface-coated with Zr was used as a positive electrode active material.
[0132] Comparative Example 4: Manufacture of secondary battery A negative electrode, a positive electrode, and a secondary battery were manufactured in the same manner as in Example 2, except that the first negative electrode active material of Example 1 (artificial graphite in the form of secondary particles formed by coarsening primary particles of carbon artificial graphite and having no carbon coating layer) was used for both the lower layer slurry and the upper layer slurry.
[0133] Secondary battery characteristic evaluation Experimental example 1: Battery life performance evaluation The lithium secondary batteries of Example 1 and Comparative Examples 1 and 2 were initially charged and discharged once using an electrochemical charger / discharger. At this time, charging was performed by applying a current at a current density of 1.5C rate up to a voltage of 4.47V, and discharging was performed at the same current density up to 3.0V. Such charging and discharging was performed a total of 1,000 times.
[0134] During the above-mentioned charging and discharging process, the voltage and capacity of the positive and negative electrodes included in each battery were measured.
[0135] From the measurement results, the capacity retention rate of each battery was calculated as follows and is shown in FIG.
[0136] Capacity retention rate (%) = (Capacity at each cycle / Initial capacity) x 100
[0137] Referring to FIG. 1 below, it can be seen that the lithium secondary battery of Example 1 according to an embodiment of the present invention exhibits a very high capacity retention rate of 80% or more even after 1,000 charge / discharge cycles compared to the lithium secondary batteries of Comparative Examples 1 and 2.
[0138] The lithium secondary batteries of Example 2 and Comparative Examples 3 and 4 were initially charged and discharged once using an electrochemical charger / discharger. At this time, charging was performed by applying a current at a current density of 1.5C rate up to a voltage of 4.47V, and discharging was performed at the same current density up to 3.0V. Such charging and discharging was performed a total of 700 times.
[0139] During the above-mentioned charging and discharging process, the voltage and capacity of the positive and negative electrodes included in each battery were measured.
[0140] From the measurement results, the capacity retention rate of each battery was calculated as follows and is shown in Figure 2.
[0141] Capacity retention rate (%) = (Capacity at each cycle / Initial capacity) x 100
[0142] Referring to FIG. 2 below, it can be seen that the lithium secondary battery of Example 2 according to an embodiment of the present invention exhibits a very high capacity retention rate of 80% or more even after 700 charge / discharge cycles compared to the lithium secondary batteries of Comparative Examples 3 and 4.
Claims
1. A secondary battery comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector and including a positive electrode active material and a binder; The positive electrode active material includes lithium cobalt oxide, The lithium cobalt oxide has a bimodal average particle size distribution including two different average particle sizes, The lithium cobalt oxide includes Al doping and is surface coated with Zr only; the negative electrode comprises a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector and including a negative electrode active material and a binder; The negative electrode active material includes a first negative electrode active material which is an artificial graphite having no carbon coating layer on its surface, and a second negative electrode active material which is an artificial graphite having a carbon coating layer on its surface, The content of Zr coated on the surface of the lithium cobalt oxide is 500 to 800 ppm based on the total weight of the lithium cobalt oxide.
2. 2. The secondary battery according to claim 1, wherein the lithium cobalt oxide comprises large particles having an average particle size of 11 μm to 30 μm and small particles having an average particle size of 1 μm to 10 μm.
3. 3. The secondary battery according to claim 1, wherein the content of Al doped in the lithium cobalt oxide is 1,000 to 10,000 ppm based on the total weight of the lithium cobalt oxide.
4. 4. The secondary battery according to claim 1, wherein a weight ratio of the first negative electrode active material to the second negative electrode active material is 1:99 to 99:
1.
5. The secondary battery according to claim 1 , wherein the negative electrode active material layer is a single layer including the first negative electrode active material and the second negative electrode active material.
6. 5. The secondary battery according to claim 1, wherein the negative electrode active material layer is a double layer including a lower layer region including the first negative electrode active material and an upper layer located on the lower layer region and including the second negative electrode active material.
7. 7. The secondary battery of claim 1, wherein the content of the carbon coating layer is 0.5% to 10.0% by weight based on the total weight of the artificial graphite having the carbon coating layer.
Citation Information
Patent Citations
High-voltage lithium cobalt oxide positive electrode active material and preparation method and application thereof
CN111900359A
Lithium metal oxide particles coated with a mixture of core material elements and one or more metal oxides.
JP2014523840A
Positive electrode active material for lithium secondary battery, manufacturing method thereof, and lithium secondary battery including the same
JP2016046240A
Lithium ion secondary battery
JP2018113167A
Negative electrode active material for lithium secondary battery and negative electrode for lithium secondary battery containing the same
JP2018523912A